The Sociolects of Antique Merchants in the Ular Market Medan - Sisi Rosida sisi; Rizky Vita Losi (ITScience (Information Technology and Science), 2022)
The Ular Market in Medan facilitates buying and selling of antiques, making this place often visited by antique connoisseurs. This study examines the sociolects of antique merchants in the Ular Market, Medan. Sociolect is identical to language variations that are formed due to social factors. The purpose of this study was to describe the forms of sociolects and the factors causing the creation of the language variation of the antique merchants in the Ular Market. In this study, the researcher applied a qualitative study with a descriptive approach. Results showed that sociolects of antique merchants in the Ular Market were formed in three varieties: (1) lexical variations in Medan Malay vocabulary, (2) phonological variations indicated by the clarity of vowels /a/ and /e/ and the shift of the pronunciation of vowel /?/ to vowel /e/, and (3) syntactic variations established by the Medan dialect in which the language develops in the local socio-cultural environment. Furthermore, the factors that cause the sociolects are educational factors (merchants come from mountainous areas so they do not receive high education) and socio-cultural factors (merchants stick to the strong family sense so that the duration of using their local language is longer).